Optimization of multipath transmission path scheduling based on forward delay in vehicular heterogeneous network - Haitao ZHAO; Yue CHEN; Tangwei ZHANG; Qixing ZHU; Hongbo ZHU (Tongxin xuebao)
In order to solve the problem that the data packets were out of order at the receiving end in the multipath transmission,which greatly reduced the transmission performance,an optimization algorithm was proposed for multipath transmission path scheduling based on forward delay in the vehicle heterogeneous network.The main idea of the proposed algorithm was to schedule data packets through a concurrent path according to the forward delay and throughput difference estimated by the sender.A simulation experiment was carried out on NS-3.The simulation results show that compared with the previous algorithm,the proposed algorithm has better performance than other algorithms in reorder-buffer-occupancy density (RBD) and throughput.The problem of out-of-order data packets at the receiving end is significantly reduced,and the total system throughput and network utilization have been improved.